2023
DOI: 10.1088/1748-605x/acb412
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of vascular endothelial cell-derived exosomes modified with vascular endothelial growth factor in steroid-induced femoral head necrosis

Abstract: Steroid-induced avascular necrosis of the femoral head (SANFH) is an intractable orthopedic disease. This study investigated the regulatory effect and molecular mechanism of vascular endothelial cell (VEC)-derived exosomes (Exos) modified with vascular endothelial growth factor (VEGF) in osteogenic and adipogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in SANFH. VECs were cultured in vitro and transfected with adenovirus Adv-VEGF plasmids. Exos were extracted and identified. In vitro/vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“… 127 Studies have shown that EVs secreted by ECs (EC-EVs) can improve the activity and functions of osteocytes induced by steroids. 128 , 129 Mechanistically, EC-EVs play an antiosteoporotic role by inhibiting osteocyte ferroptosis. 129 A similar phenomenon occurs when EVs are derived from endothelial progenitor cells (EPCs), which can reverse osteoporosis induced by large doses.…”
Section: The Potential Role Of Evs Derived From Different Sources In ...mentioning
confidence: 99%
“… 127 Studies have shown that EVs secreted by ECs (EC-EVs) can improve the activity and functions of osteocytes induced by steroids. 128 , 129 Mechanistically, EC-EVs play an antiosteoporotic role by inhibiting osteocyte ferroptosis. 129 A similar phenomenon occurs when EVs are derived from endothelial progenitor cells (EPCs), which can reverse osteoporosis induced by large doses.…”
Section: The Potential Role Of Evs Derived From Different Sources In ...mentioning
confidence: 99%
“…( Table 1 ). For example, the activation of MAPK/ERK, SMAD, Wnt/β-catenin, and cAMP signaling is facilitated by the secretion of exosomes and cytokines derived from endothelial cells, which foster the formation of osteoblasts and chondrocytes [ 24 , 25 , 26 , 27 , 28 , 29 ]. By modulating histone lactylation, endothelial cell-derived metabolites like lactate stimulate the osteogenic differentiation of mesenchymal stem cells [ 30 ].…”
Section: Endothelial Cells Orchestrate Angiogenesis–osteogenesis Coup...mentioning
confidence: 99%